Self-Medication Behavior and Contributing Factors Among Libyan Students - Atia, Ahmed; Omhani Alsodani,; Shahed Zuto,; Rahaf Shawesh,; Shada Ashamli, (AlQalam Journal of Medical and Applied Sciences, 2025)
Self-medication is a global issue, especially in areas with limited healthcare access. While offering temporary relief, it poses risks like misdiagnosis, adverse reactions, and antibiotic resistance. This practice is common among students and can impair health. This study evaluates the prevalence, knowledge, and factors influencing self-medication among medical and non-medical students. The study included 180 university students, surveyed by using an electronic questionnaire comprising 14 questions. Among the 180 participants, 75.6% practiced self-medication, with 82.2% being female, who were more likely to self-medicate compared to males (17.8%), with a p-value of 0.03. Key reasons for self-medication included previous experience (55.1%, p-value = 0.01), easy access to medications (40.4%, p-value = 0.02), and advice from family/friends (40.4%, p-value = 0.03). Additionally, 31.5% cited avoiding doctor visits as a reason (p-value = 0.04), and 64.4% were aware of the risks of self-medication (p-value = 0.04). These findings underscore the impact of gender, accessibility, and awareness on self-medication behavior. While awareness of risks is moderate, there is a need for increased education and stricter regulations to promote safer healthcare practices. The findings emphasize the importance of addressing these factors to reduce self-medication.